The relation between energy consumption and developed land; a model for the metropolitan area of Barcelona - Jorge Cerda; Yraida Romano; Claudia Perez; Josep Roca (European Regional Science Association (ERSA), 2011)
The study of the developed land and the energy consumption is part of a main project, which objective is the development of a model for the evaluation of the environmental and energy efficiency of the interaction (mobility) and land use structure (called as 'territorial functionality'), applied to the metropolitan area of Barcelona . One of the most important points of the main project is the modeling of energy consumption, and developed land produced by the territorial functionality. This paper presents the calibrations results of econometrics models (log-log) for developed land, and electricity consumption. The used information for those models was; built surface by activity (cadastre), coverings of land uses of Catalonia (CREAF), electric consumption by economic activity (CNAE), meteorological variables, and operating time of activities. The analysis was for the 164 municipalities of the metropolitan area of Barcelona. The electric consumption was analyzed in different categories of activities like as residential, industrial, trade, financial services, hotels, transport, education, public lighting, etc. The artificial area was differentiated in three categories; cadastre surface, streets, and developed land without cadastre. Overall, the results show that the extension of developed land depends (with 0.8 R2) mainly from single-family homes, followed by industrial activities, and finally sport activities. The trade activities induce a contraction of developed land, result that is consistent with agglomeration economies. The different models calibrated for energy consumption show a strong dependence (with R2 between 0.5 and 0.9) first with built surface, and second with other variables such as weather condition in the municipality (minimum temperature in summer), and average operating time of the activities (mean work time, shopping time, etc). Finally, the electric consumption by public lighting depends significantly on the developed land, representing the union between the two dimensions of the study.
Keywords: 330